Genetic improvement of tomato by targeted control of fruit softening - Uluisik, Selman; Chapman, Natalie H; Smith, Rebecca A.; Poole, Mervin; Adams, Gary; Gillis, Richard B; Besong, Tabot M D; Sheldon, Judith; Stiegelmeyer, Suzy M.; Perez, Laura; Samsulrizal, Nurul Hidayah; Wang, Duoduo; et al. (Nature Publishing Group, 2016)
Controlling the rate of softening to extend shelf life was a key target for researchers engineering genetically modified (GM) tomatoes in the 1990s, but only modest improvements were achieved. Hybrids grown nowadays contain 'non-ripening mutations' that slow ripening and improve shelf life, but adversely affect flavor and color. We report substantial, targeted control of tomato softening, without affecting other aspects of ripening, by silencing a gene encoding a pectate lyase.